PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN SASTRA - Maman Suryaman (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Character Education through Literature Learning. One of the importantaspects in appropriate literature learning is character education. Based on theresults of several studies, some conclusions can be drawn. First, essentiallyliterature is a medium of mental and intellectual enlightenment, the mostimportant aspect in character education. Second, there are a variety of literaryworks that need appreciating as they are important in the character development.Third, literature learning relevant to the character development is one that enableslearners to develop their awareness of reading and writing as importantprerequisites for the character development. Fourth, literary books relevant to thecharacter development are those with beautiful language capable of making thereaders moved, containing high humanistic values, and encouraging the readers totreat other people and creatures well.Keywords: literature, literature learning, character education